(untitled) (Perner’s Contacts, 2022)
This article presents the results of a survey of urban public transport users in the Czech Republic, which focused on evaluating the characteristics of urban PT stops and the importance of various attributes of public transport travel. In general, the highest rated items are those related to cleanliness, comfort and safety. This applies both to stops and vehicles. These attributes are more important for respondents of increasing age and education. Furthermore, among the essential types are those that contribute to the efficiency of public transport (reliability of transportation, information for passengers and the possibility of choosing between connections). While, for example, information boards with current departures are more important, especially for older adults, seniors and students, students will appreciate a mobile application with this information more. The items in both inventories, especially those rated generally the highest, are not so important for respondents who use public transport frequently. For these passengers, the efficiency of public transport, i.e. the total travel time, is essential. Among the items rated generally as less important are related to barrier-free access to a bus stop or a public transport vehicle. However, these attributes are significantly more important for specific groups of respondents: the elderly, respondents with small children and non-working pensioners.